Digital wayang kulit model for learning mathematics - Ahmad, Jasni; Jamaludin, Zulikha (Asian Research Publishing Network (ARPN), 2016)
We propose a model that illustrates how digital Wayang Kulit (DWK) helps students learn mathematics in primary school.Wayang Kulit (WK) is unlikely to last long due to lack of safeguarding. Hence, there is an urgent need to preserve this cultural heritage from extinction.Drawing from the facts that there is deficient in performance of primary school children in mathematics. Henceforward, we proposed a conceptual model that illustrates how digital WK helps students learn mathematics. We use the model to develop a DWK using RAD method.The DWK, given a persona name eWayCool, demonstrates how WK can be transformed into mathematics’ learning object. In order to support the engagement and entertainment in DWK, the needs for effective interaction design with three dimensions of Interaction Design (IxD) theory are added.The 15-questions USE was distributed to measure the performance of DWK.The students perceived e-WayCool as useful (79%) and satisfying (83.4%).The result showed that the students perceived high satisfaction towards the proposed digital WK.It indicates DWK is effective for mathematics learning at primary level, and as such, the model proposed can be generalised to a wider domain.